2019
DOI: 10.1016/j.ceramint.2019.04.191
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sintering temperature on conductivity and mechanical behavior of the solid electrolyte LATP

Abstract: To warrant long-term reliability for application of electrolytes in solid state batteries also mechanical properties have to be considered. Current work concentrates on Li 1+x Al x Ti 2-x (PO 4 ) 3 (LATP), which based on its conductivity is a very promising material. Effect of sintering temperature (950, 1000, 1050, 1100 °C) on mechanical properties and conductivity was tested.Impedance tests were carried out and as main focus of the work the mechanical behavior of LATP samples was determined. The impedance te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 61 publications
2
39
0
Order By: Relevance
“…However, issues related to crack formation or delamination of interfaces can deteriorate material properties and battery performance [1]. In fact, a large number of publications are available on different synthesis approaches and resulting conductivities of LATP [6][7][8][9][10][11][12][13][14][15], but only a limited number of publications have addressed the failure-relevant mechanical properties of solid electrolytes [6,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, issues related to crack formation or delamination of interfaces can deteriorate material properties and battery performance [1]. In fact, a large number of publications are available on different synthesis approaches and resulting conductivities of LATP [6][7][8][9][10][11][12][13][14][15], but only a limited number of publications have addressed the failure-relevant mechanical properties of solid electrolytes [6,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…[16,19,[21][22][23][24][25] Thus, thermal and chemical compatibilities of CAM/SSE at the processing temperature and (electro)chemical properties of the CAM/SSE interphase are the determining factors for the choice of CAM/SSE combinations.Phosphate-based NASICON-type Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 (LATP) is attractive to be employed as the SSE for ASSBs due to its competitive ionic conductivities and good chemical stability in ambient atmosphere. [26][27][28] LATP is considered to have better thermal stability with phospho-olivine LiMPO 4 (M: Fe, Mn, Co, Ni) cathodes because the oxygen atoms are tightly bound to P with the strong covalent bonds in both LATP and LiMPO 4 . [29] It was reported that the mixture of LATP and different phosphate-based CAMs such as LiFePO 4 (LFP), LiCoPO 4 , and LiMn 0.5 Fe 0.5 PO 4 showed promising thermal stabilities at elevated sintering temperatures around 700-800 °C in an inert atmosphere.…”
mentioning
confidence: 99%
“…Table 3 shows a comparison of ionic conductivity of LATP sintered at various conditions. In our sol-gel method, high conductive LATP was obtained comparing with other studies at similar sintering conditions [35][36][37][38]. Some studies used sintering additive such as LiF, LiBO 2 and so on.…”
Section: Discussionmentioning
confidence: 64%